The Role of a Prone Setup in Breast Radiation Therapy - Huppert, Nelly; Jozsef, Gabor; DeWyngaert, Keith; Formenti, Silvia C. (Frontiers in Oncology, 2011)
Most patients undergoing breast conservation therapy (BCT) receive radiotherapy in the supine position. Historically, prone breast irradiation has been advocated for women with large pendulous breasts in order to decrease acute and late toxicities. With the advent of CT planning, the prone technique has become both feasible and reproducible. It was shown to be advantageous not only for women with larger breasts but in most patients since it consistently reduces, if not eliminates, the inclusion of heart and lung within the field. The prone setup has been accepted as the best localizing position for both MRI and stereotactic biopsy, but its adoption has been delayed in radiotherapy. New technological advances including image-modulated radiation therapy (IMRT) and image-guided radiation therapy (IGRT) have made possible the exploration of accelerated fractionation schemes with a concomitant boost to the tumor bed in the prone position, along with better imaging and verification of reproducibility of patient setup. This review describes some of the available techniques for prone breast radiotherapy and the available experience in their application. The NYU prone breast radiotherapy approach is discussed, including a summary of the results from several prospective trials.